Is antral membrane balloon elevation truly minimally invasive technique in sinus floor elevation surgery? A systematic review - Huda Moutaz Asmael (International Journal of Implant Dentistry, 2018)
Abstract Background Minimally invasive antral membrane balloon elevation was introduced as a less traumatic technique in sinus floor elevation surgery. This is the first systematic review to assess the results of previous studies utilizing this technique. Aims of the study The objectives of this study were to assess the bone gain, sinus augmentation success rate, implant survival rate, and complications with minimally invasive antral membrane balloon elevation technique in comparison with the sinus floor elevation by traditional transalveolar technique (Summers’ technique). Materials and methods An electronic search including MEDLINE (PubMed) and Cochrane database sites was conducted and supported by manual searching for articles on minimally invasive antral membrane balloon elevation from 1945 to 16 January 2017. Sometimes the researchers were contacted to fill the missing information which was not mentioned in their articles. Results The extracted articles which involved utilization of balloon technique in maxillary sinus floor elevation surgery were 27 articles, among which only 10 articles met the inclusion criteria. The average of schneiderian membrane perforation with minimally invasive antral membrane balloon elevation (MIAMBE) technique was 6.76%. The sinus augmentation success rate ranged from 100 to 71.4% with average of 91.6%. Bone gain with this technique could reach for more than 10 mm with an average of 6.96 mm. Conclusions Minimally invasive antral membrane balloon elevation combined the beneficial points of both lateral window approach and transalveolar approach in which it produced ≥ 10 mm of gained bone in minimally invasive manner. Anyhow, long follow-up period is needed to accurately identify the long-term success rate of dental implants placed with this technique.